'Wh-on-earth' in Chinese speakers' L2 English: Evidence of dormant features. (October 2014) - Yuan, Boping
Adopting a decompositional approach to items in the lexicon, this article reports on an empirical study investigating Chinese speakers' second language (L2) acquisition of English wh-on-earth questions (i.e. questions with phrases like what on earth or who on earth ). An acceptability judgment task, a discourse-completion task and an interpretation task were used in the study, and the results indicate that in Chinese speakers' L2 English, the form of wh-on-earth can be learned and stored in a native-like manner, but without being endowed with fully elaborated features. A distinction between active features and dormant features in L2 lexicon is made in the analysis, and it is argued that features transferred from learners' L1 to their L2 are likely to lose their vigour and vitality in their L2 lexicon and become dormant if there is no evidence in the target language input to confirm or disconfirm them. A typical consequence of a dormant feature is random behaviours of a related structure in L2 learners' production and interpretation. The results of the study show that semantic features, discourse features as well as morphosyntactic features can become dormant in L2 lexicon.